Development of Student Worksheet Based on Inquiry and Internet Assisted Learning to Practice Critical Thinking Skills in Submateries of Reaction Rates. - Kuny Abidatul Mahmudah; Bertha Yonata (Jurnal Pendidikan dan Pembelajaran Kimia, 2020)
This study aims to determine the feasibility based of Inquiry student worksheets based on Internet Assisted Learning in the reaction rate submaterial to practice critical thinking skills of class XI SMA students. The development research design uses the 4-D method (Define, Design, Develop, and Dissiminate). In this research it is up to the development stage. The trial was carried out on 24 high school class XI students who had not received material on the reaction rate on November 9-20 2020. The research instrument consisted of a review sheet, a validation sheet, a student response questionnaire, a knowledge test sheet, and a critical thinking skill test sheet. The results showed that the student worksheet was very feasible based on the assessment of the validator and student responses of ≥ 81% and achieving a value of ≥ 75 according to the criteria for minimum learning completeness. The validator's assessment based on the eligibility of the content, language, presentation, and graphic criteria showed the percentage of 98.6%, 86.4%, 85,4%, and 100%  in the very valid category. Student response shows a positive response assessment based on the eligibility of the content, language, presentation, and graphic criteria showed the percentage criteria of content is 91.8% , language is 81.7%, presentation is 85%, and graphic 96.7%. The results of the knowledge test obtained an n-gain score of 0.85 in the very high category. The results of the creative thinking skills test obtained an n-gain score of 0.795 in the very high category.